Molecular and presymptomatic analysis of a Moroccan Lynch syndrome family revealed a novel frameshift MLH1 germline mutation - Moufid, Fatima Zahra; Bouguenouch, Laila; El Bouchikhi, Ihssane; Iraqui Houssaini, Mohamed; Ouldim, Karim (Turkish Journal of Gastroenterology, 2018)
Abstract Lynch syndrome (LS) is an autosomal dominant disorder characterized by an increased risk of extracolonic cancers and early age of onset. It is associated with germline mutations in the DNA mismatch repair (MMR) genes. We report a case of a patient with colorectal cancer referred to our medical genetics department for molecular analysis and genetic counseling. The proband is a 64-year-old woman diagnosed with a tumor of the cecum. Histopathological examination showed a moderately differentiated mucinous adenocarcinoma categorized by pT3 N0. Analysis of her pedigree revealed three siblings who had colon cancer, as well as one relative with brain cancer. Based on these findings, molecular genetic investigation was found to be necessary in order to identify the disease-causing mutation. Immunohistochemistry staining of MMR proteins was performed on the tumor sample of the index proband. Mutational analysis of the MLH1/MSH2 genes was carried out. Analysis was extended to the family members and the general population. This led to the identification of a heterozygous frameshift duplication in the MLH1 gene at position 910 (c.910dupG). Three siblings had inherited the mutation from their mother, two of whom were asymptomatic at the time of diagnosis. To the best of our knowledge, this is a novel pathogenic duplication that has not been reported in the databases and literature. The outcome of the present case suggests that this mutation was the primary cause of LS in the family. Cite this article as: Moufid FZ, Bouguenouch L, El Bouchikhi I, Houssaini MI, Ouldim K. Molecular and presymptomatic analysis of a Moroccan Lynch syndrome family revealed a novel frameshift MLH1 germline mutation. Turk J Gastroenterol 2018; 29: 701-4.